The Development of Adults and the Elderly - Fauziah Nasution; Afdilla Zulkarnain; Fadhilah Paramitha; Nasta Fauzia Adhani Nst; Rizka Dewi salsabila (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study discusses the developments occurring in adults and the elderly, covering physical, psychological, social, and economic challenges. The increasing elderly population worldwide reflects a rise in life expectancy, but it also presents various issues such as physical health decline, social isolation, changes in family dynamics, and challenges in retirement. This research uses a qualitative descriptive approach to describe the experiences and adaptive strategies employed by older adults and the elderly in facing these changes. The findings indicate that family support, healthy lifestyles, and access to adequate healthcare services play a crucial role in improving the quality of life for the elderly. Moreover, the presence of nursing homes and elderly communities provides solutions to social changes and the limitations of family roles in supporting the elderly. This study concludes that, although the elderly face many challenges, those who can accept these conditions positively are able to enjoy their old age wisely, happily, and meaningfully.